ORIENTALISME DALAM KAJIAN HADIS: Telaah Historis, Ruang Lingkup, dan Pemikiran Kaum Orientalis terhadap Tradisi Hadis Nabi - Indra Wahyuddin; Syamsu Syauqani (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
This study discusses orientalism in the context of hadith studies by highlighting the historical aspects, scope, and thoughts of orientalists towards the Prophetic tradition of hadith. The involvement of orientalists i.e. Western scholars researching Islam has created its own dynamics in the study of hadith, especially in terms of authenticity, transmission and narration methodology. This study aims to explore the background of the emergence of orientalism, understand the frame of mind of the orientalists, and analyze their approaches in understanding the Prophetic traditions. Historically, orientalism emerged as a response to the Western world's interest in the East, which later developed into a systematic study of various aspects of Islamic civilization, including hadith. Orientalists such as Ignaz Goldziher, Joseph Schacht and others have criticized the validity of the hadith, which are considered to be more influenced by political and social dynamics rather than coming directly from the Prophet Muhammad. In their scope, orientalist studies of hadith were not only limited to sanad criticism but also included an analysis of the sociological, historical and cultural context in which the hadith developed. These ideas have had a significant impact in the academic world, both constructive and controversial. This study uses a qualitative approach with a library research method, in order to present a comprehensive review of orientalist narratives in hadith studies. It is hoped that this study can provide an objective critical perspective on the contributions and challenges offered by orientalism in understanding hadith as one of the main sources of Islamic teachings.